LRS Bianchi Type-I Dark Energy Cosmological Models in General Scalar Tensor Theory of Gravitation. (12th June 2013) - Rao, V. U. M.; Neelima, D.
Abstract : Locally rotationally symmetric (LRS) Bianchi type-I dark energy cosmological model with variable equation of state (EoS) parameter in (Nordtvedt 1970) general scalar tensor theory of gravitation with the help of a special case proposed by (Schwinger 1970) is obtained. It is observed that these anisotropic and isotropic dark energy cosmological models always represent an accelerated universe and are consistent with the recent observations of type-Ia supernovae. Some important features of the models, thus obtained, have been discussed.